Correlation Between Electroretinogram and Visual Prognosis in Metallic Intraocular Foreign Body Injury - Mai, Xiaoting; Ling, Fangyi; Gong, Yuting; Chen, Jialin; Lin, Hongjie; Chen, Haoyu (Frontiers in Medicine, 2021)
Purpose: This study aims to investigate the correlation between electroretinogram (ERG) and visual outcome in eyes with metallic intraocular foreign body (IOFB) injury. Methods: Cases with metallic IOFB injuries with preoperative ERG from January 2008 to May 2020 were reviewed retrospectively. Five ERG responses were recorded, including rod response, maximal response, oscillatory potentials, cone response, and 30-Hz flicker. The results were compared between the affected and the contralateral eyes. All patients received surgery to remove IOFBs. The correlation between amplitudes, implicit times, and grades of ERG with final best-corrected visual acuity (BCVA) was analyzed. Results: A total of 33 eyes of 33 patients were included. The eyes with IOFB had generally delayed implicit time and reduced amplitude in all waves. The maximum change was found in oscillatory potentials S3 and N1 (0.42 ± 0.42 and 1.95 ± 1.97 of the fellow eyes, respectively, p < 0.05). All amplitudes were negatively correlated with the final BCVA (rs: −0.676 to −0.459, all p < 0.05). In contrast, all implicit times were positively correlated with final BCVA, although, some of them were not statistically significant (rs: 0.035 to 0.687). Among them, oscillatory potential P3 has the highest correlation coefficient (rs = 0.687, p < 0.001). All grades of ERG waves were statistically correlated with the final BCVA (rs: −0.596 to −0.664, all p < 0.001). Conclusions: ERG can be used to assess visual outcome in metallic IOFB injury after surgery. Oscillatory potentials provided the most significant responses.